2023
DOI: 10.3390/w15020325
|View full text |Cite
|
Sign up to set email alerts
|

Past and Present Environmental Factors Differentially Influence Genetic and Morphological Traits of Italian Barbels (Pisces: Cyprinidae)

Abstract: Local adaptation and phenotypic plasticity can lead to environment-related morphological and genetic variations in freshwater fish. Studying the responses of fish to environmental changes is crucial to understand their vulnerability to human-induced changes. Here, we used a latitudinal gradient as a proxy for past and present environmental factors and tested its influences on both genetic and morphological patterns. We selected as a suitable biogeographic model, the barbels, which inhabit 17 Adriatic basins of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 97 publications
(118 reference statements)
0
1
0
Order By: Relevance
“…The ecological niche of B. barbus highly overlaps with the ecological niche of B. plebejus (i.e., fluvio-lacustrine ecophenotype (Kottelat and Freyhof, 2007)), favouring widespread introgressive hybridization (Meraner et al, 2013;Zaccara et al, 2014;Buonerba et al, 2015). It is possible to discriminate morphologically the two species of barbel from the number of scales along the lateral line and from the shape and microstructure of the dorsal fin, but this discrimination can be unreliable due to the variability of these traits within the same species (Bianco, 2003;Kottelat and Freyhof, 2007;Quadroni et al, 2023a). Moreover, the occurrence of hybridisation further hinders the morphological discrimination (Tsigenopoulos et al, 2002;Gante et al, 2008;Buonerba et al, 2015) making the use of molecular techniques necessary (Zaccara et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The ecological niche of B. barbus highly overlaps with the ecological niche of B. plebejus (i.e., fluvio-lacustrine ecophenotype (Kottelat and Freyhof, 2007)), favouring widespread introgressive hybridization (Meraner et al, 2013;Zaccara et al, 2014;Buonerba et al, 2015). It is possible to discriminate morphologically the two species of barbel from the number of scales along the lateral line and from the shape and microstructure of the dorsal fin, but this discrimination can be unreliable due to the variability of these traits within the same species (Bianco, 2003;Kottelat and Freyhof, 2007;Quadroni et al, 2023a). Moreover, the occurrence of hybridisation further hinders the morphological discrimination (Tsigenopoulos et al, 2002;Gante et al, 2008;Buonerba et al, 2015) making the use of molecular techniques necessary (Zaccara et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the allometry of the otoliths and scales of individuals in this research affected the results of Procrustes ANOVA, but this limitation was corrected by regression and further analysis of regression residuals. Previous research suggested that local adaptation and phenotypic plasticity can lead to environmental-related morphological and genetic variations in freshwater fish, as a response to latitude, thermal and hydrological conditions (Quadroni et al, 2023). However, it was found that the fish scale form was least effective in discriminating populations from nearby areas but better when populations are more geographically dispersed (Ibáñez et al, 2007) or when there is a previously recorded pattern for each location (Ibáñez, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Fish morphometric variation among stocks has been shown to be a useful tool to describe fish spatial distributions and identify different population units, as fish body morphological differences (e.g., length, width and depth) can be associated with genetic background [10][11][12] or processes of phenotypic plasticity as a response to different environmental conditions [13][14][15]. Exposure to variations in factors, such as temperature, salinity and food availability, can result in different behavioral patterns (e.g., aggregation, migration and others) and the adoption of different adaptation strategies, which could be reflected in fish morphometric features and contribute to the definition of different phenotypic stocks [16][17][18]. The truss network system is a geometric morphometrics method commonly used for stock discrimination purposes that provides information on phenotypic traits [9,19,20].…”
Section: Introductionmentioning
confidence: 99%